Structural and functional analysis reveals the catalytic mechanism and substrate binding mode of the broad-spectrum endolysin Ply2741 - Shuang Wang; Xinxin Li; Jiahui Ma; Xiaochao Duan; Haiyan Wang; Linkang Wang; Dayue Hu; Wenwu Jiang; Xiangmin Li; Ping Qian (Virulence)
The emergence of antibiotic-resistant bacteria has attracted interest in the field of endolysins. Here, we analyzed the diversity of Streptococcus endolysins and identified a new endolysin, Ply2741, that exhibited broad-spectrum bactericidal activity. Our results demonstrated that Ply2741 could effectively eradicate multidrug-resistant gram-positive pathogens in vitro and in vivo. Structural analysis revealed that the bactericidal activity of Ply2741 depends on the classic “Cys-His-Asn” catalytic triad. Site-directed mutagenesis results further identified that the conserved residue Gln29, located near the catalytic triad, also contributes to the lytic activity of Ply2741. Furthermore, the key residues (R189 and W250) in the Ply2741 cell wall binding domain (CBD) responsible for binding to peptidoglycan were revealed by molecular docking and fluorescence-activated cell sorting (FACS) analysis. Ply2741 demonstrates a broad lytic spectrum, with significant bactericidal activity against Enterococcus, Staphylococcus, and Streptococcus and species. To the best of our knowledge, we found that residue Gln29 participated in the lytic activity of endolysin for the first time. Additionally, we systematically elucidate the binding mode and key residues of the Ply2741CBD. This study proposes Ply2741 as a potential antibiotic substitute and provides a structural basis for the modification and design of endolysins.